PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 25 PEKANBARU - urdin, Landriani; Munjiatun, Munjiatun; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was motivated by the percentage of students who achieve KKM 75 at mid even semester of the year 2014 to 2015 is even lower. From 29 students only 14 (48.27%) of students who reached KKM and 15 (51.72%) students who have not reached KKM with an average of 68.97. This is because teacher rarely used learning models during the learning process in the classroom, the teacher seldom used the teaching tools ,the teacher was more active than students. From these problems need to be done to implement the action research learning based the students’ problem. Where the research was in SD Negeri 25 Pekanbaru with research subjects were students of class IV and as many as 29 students, male students and 17 female students 12 people. This study was carried in 2 cycles. Instrument collecting data in this study is the observation sheet teacher activity, student activity observation sheet and test sheet daily tests. Obesrvasi results showed that the activity of teachers and students have increased. The activities of teachers in the first cycle both categories increased 63.64% in the second cycle into 85.25% very good category. Activity of students in the first cycle both categories increased 61.36% in the second cycle into 81.82% very good category. The results showed that the learning outcomes of students has increased, the initial score with an average of 68.97 incomplete categories increased in the first cycle to 78.79 categories is not exhaustive, and the second cycle increased to 87.41% complete category. Mastery learning students’ was on score of 48.27% reaching KKM, in the first cycle showed that 65.51% of students who reached the KKM has been established, on the second cycle increased to 86.23% of students who reached KKM and a predetermined percentage of completeness. From the above shows that through the application of learning mathematics based on students’ problem improved learning outcomes of fourth grade students and 25 elementary school lesson Pekanbaru in year of education 2014-2015.Keywords: Problem Based Learning Model, Mathematics Learning Outcomes